Dental Arch Dimensions in Saudi Adults - Omar Hamad Alkadhi; Sarah Fahad Almahfouz; Hana Abdulmajeed Tokhtah; Lamia Abdulaziz Binhuwaishel (International Journal of Dentistry)
Objective. The aim of this study was to investigate the arch dimensions (width, length, and depth) in Saudi Arabia. Materials and Methods. 169 orthodontic models (73 males and 96 females) made of white stone were selected according to inclusion criteria. Measurement of arch dimensions was taken including width, length, and depth at different reference points. Differences between males and females were tested using independent samples t-test. Results. The sample comprised subjects aged 18–33 years old. Most measurements showed higher values for males compared to females. Saudi males showed smaller intercanine widths compared to Caucasians and Southern Chinese but larger widths in females compared to Caucasians and smaller widths compared to Southern Chinese. Saudi males and females showed larger intermolar widths compared to Caucasians but smaller intermolar widths compared to Southern Chinese. For arch length, Saudis showed longer arches compared to Yemenis for both males and females but smaller palatal depths compared to Yemenis. Conclusions. Differences in intercanine width, intermolar width, and palatal length and depth were found between Saudis and other nationalities. Male and female participants had differences in most of the measurements.